Pratt's essential biochemistry - Pratt, Charlotte W.; Cornely, Kathleen (John Wiley & Sons, 2018)
Pratt's essential biochemistry, global edition aims to provide a solid foundation in biochemistry, presenting complete, up-to-date information while focusing on the practical aspects of biochemistry as it applies to human health, nutrition and disease. It presents a broad, but not overwhelming coverage of basic biochemical concepts that focus on the chemistry behind biology, structure-function relationships, transformation of energy and how genetic information is stored and made accessible.